A bizalom éjszakájában: Holokausztszólamok Borbély Szilárd írásművészetében - Valastyán , Tamás (Studia Litteraria, 2016)
The configuration of faith and desperation constitutes a pattern in modernity that appears in different ethical, epistemic and aestethic contexts. I think that this pattern is outlined in the poetry and essays of Szilárd Borbély and what is more, it has essential power. We may say that the existence after the holocaust can be measured by its own relations in contrast to genocide. Existence is already a relation to genocide. In my essay I present the attempts of Borbély Szilárd to show that horrible measurement. Or more exactly: I cannot explore the characters of his deep, colourful laminated, and sometimes controversial answers; I just focus on three points: At first I present the dilemmas of dealing with the poetic life-work of Miklós Radnóti; then I discuss the polemic relation to the holocaust interpretation of Kertész Imre; and finally I try to approach the poems in A Testhez [To the Body] which derive their truth from the memory of holocaust survivors.